Dermatofibrosarcoma Protuberans of the Forehead: Case Report of a Rare Entity and Review of Literature - Ulrich Igor Mbessoh Kengne; Jaafar Ibn Abou Talib Thiam; Amacoumba Fall; Salif Balde; Mamadou Ndiaye; Joel Gabin Konlack Mekontso; Gorgui Sarr; Etienne Tossou Zoure; Mamadou Sow; Sidy Ka (Case Reports in Oncological Medicine)
Dermatofibrosarcoma protuberans (DFSP) is a rare soft tissue sarcoma originating from fibroblasts in the dermal connective tissue, comprising approximately 1% of all soft tissue sarcomas. While most cases involve the trunk and extremities, only 10%–15% occur in the cephalic region, representing less than 1% of all head and neck neoplasms. DFSP is notable for its high propensity for local recurrence following surgical excision and its low metastatic potential. We report a case of recurrent DFSP of the forehead extending to the anterior wall of the left frontal sinus, without brain involvement, in a 33-year-old male with a history of three prior wide local excisions. A multidisciplinary cancer team recommended systemic imatinib therapy. This case highlights the challenges of managing DFSP in an uncommon location, underscoring the importance of a multidisciplinary approach in addressing recurrent and complex presentations.